2020
DOI: 10.1093/cercor/bhaa326
|View full text |Cite
|
Sign up to set email alerts
|

NECAB1 and NECAB2 are Prevalent Calcium-Binding Proteins of CB1/CCK-Positive GABAergic Interneurons

Abstract: The molecular repertoire of the “Ca2+-signaling toolkit” supports the specific kinetic requirements of Ca2+-dependent processes in different neuronal types. A well-known example is the unique expression pattern of calcium-binding proteins, such as parvalbumin, calbindin, and calretinin. These cytosolic Ca2+-buffers control presynaptic and somatodendritic processes in a cell-type-specific manner and have been used as neurochemical markers of GABAergic interneuron types for decades. Surprisingly, to date no typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 149 publications
2
18
0
Order By: Relevance
“…These include NECAB1, a calcium binding protein that specifically labels CCK+ IN cell bodies (Fig. 3 A) [ 52 ], and VGLUT3, a vesicular glutamate transporter enriched at CCK+ IN synapses ( Fig. 3 C ) [ 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…These include NECAB1, a calcium binding protein that specifically labels CCK+ IN cell bodies (Fig. 3 A) [ 52 ], and VGLUT3, a vesicular glutamate transporter enriched at CCK+ IN synapses ( Fig. 3 C ) [ 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some of these basket cells, VIP may also be expressed (Omiya et al, 2015 ; Rhomberg et al, 2018 ). Of note, a recent study has revealed that the Ca 2+ binding proteins NECAB1 and 2 are expressed in CCK/CB1, but not PV basket cells in cortical structures, including the BLA (Miczan et al, 2021 ). At the population level, half of the output synapses of CCK/CB1 basket cells target the perisomatic region (similarly to PV basket cells), whereas the other half contacts distal dendrites with a progressive decline in density toward the tip of dendrites ( Figures 2A,B ; Veres et al, 2017 ).…”
Section: Perisomatic Inhibition In Cortical Regions Originates From Three Interneuron Typesmentioning
confidence: 99%
“…These include NECAB1, a calcium binding protein that specifically labels CCK+ IN cell bodies (Fig. 3A) (Miczan et al, 2021), and VGLUT3, a vesicular glutamate transporter enriched at CCK+ IN synapses (Fig. 3C) (del Pino et al, 2017; Pelkey et al, 2020; Somogyi et al, 2003).…”
Section: Resultsmentioning
confidence: 99%